2007
DOI: 10.1007/s10126-007-9054-9
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Functionality of Probiotics in the Larviculture Food Chain

Abstract: During the past two decades, the use of probiotics as an alternative to the use of antibiotics has shown to be promising in aquaculture, particularly in fish and shellfish larviculture. This article reviews the studies on probiotics in larviculture, focusing on the current knowledge of their in vivo mechanisms of action. The article highlights that the in vivo mechanisms of action largely remain to be unravelled. Several methodologies are suggested for further in vivo research, including studies on gut microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 92 publications
2
80
0
3
Order By: Relevance
“…Higher THC of probiotic fed marron also provides better protection to the gill from parasites and bacteria pathogens which may cover and reduce respiration efficiency. Tinh et al [45] suggested that probiotic bacteria can also be active on the gills and skin of the host. Inefficient respiration during handling and live transport may contribute to marron mortality in basal diet fed marron.…”
Section: Discussionmentioning
confidence: 99%
“…Higher THC of probiotic fed marron also provides better protection to the gill from parasites and bacteria pathogens which may cover and reduce respiration efficiency. Tinh et al [45] suggested that probiotic bacteria can also be active on the gills and skin of the host. Inefficient respiration during handling and live transport may contribute to marron mortality in basal diet fed marron.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative strategy to antibiotics, probiotics have recently attracted extensive attention in aquaculture. Many reports have been published regarding application of probiotics in the aquatic environment (for review see, Ringø and Gatesoupe, 1998;Gatesoupe, 1999;Verschuere et al, 2000;Irianto and Austin, 2002;Burr et al, 2005;Gram and Ringø, 2005;Farzanfar, 2006;Tinh et al, 2008;Wang et al, 2008). Due to high cost, Norwegian Scientific Committee for Food Safety…”
Section: Prebioticsmentioning
confidence: 99%
“…(reviewed by Tinh et al 2008;Cao et al 2012). Thus, the identification of biological functions in marine microorganisms could have wide-reaching applications.…”
Section: Enzymes That Degrade Biofilm-forming Qs Signalsmentioning
confidence: 99%